Simultaneous Determination of 13 Mycotoxins in Plant Solid Beverages by UPLC-MS/MS Combined with Modified QuEChERS - Zhi LU; Yaxian LI; Fengsong LIU; Zhi GAO; Yajie LI (Shipin gongye ke-ji)
This work aimed to develop a high-throughput analytical method based on QuEChERS coupled with ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) for the determination of 13 mycotoxins in plant-solid beverages. The samples were homogenized and dissolved in water. QuEChERS method was used for pretreatment, ultrasonic extraction with 2% formic acid-acetonitrile solution, and purification with octadecylsilane bonded silica gel (C18). The extraction solution was then separated by a Kinetex F5 column, detected by a tandem mass spectrometry detector in multiple reaction monitoring mode (MRM), and quantified by matrix-matched standard calibration. The optimum conditions achieved limits of detections (LODs) in the range of 0.04~16.9 μg/kg, with correlation coefficient over 0.9916. The limit of quantifications (LOQs) were in the range 0.12~38.2 μg/kg. The recoveries in real plant-solid beverages ranged from 82.2% to 103.3%, with relative standard deviations (RSDs) below 9.0%. Moreover, the proposed method was applied to analyze mycotoxins in 18 plant-solid beverage samples, a positive detection rate of 4/18 was obtained, and the detected analytes included deoxynivalenol and fumonisin B3. This proposed method has the advantages of simple operation, low cost, high sensitivity and accuracy, which can be used for the high-throughput screening of multiple mycotoxins in plant-solid beverages.